Some Biochemical Perturbations May Modify the Understanding of Trypanotolerance in the West African Dwarf Sheep Infected With and - Davinson C Anyogu; Shodeinde VO Shoyinka; John I Ihedioha (SAGE Publishing, 2020)
Trypanosomes are single-celled protozoa that cause severe diseases in both humans and livestock in sub-Saharan African countries. The disease in the West African Dwarf (WAD) sheep is often neglected due to the issue of trypanotolerance. The current study is aimed to evaluate some biochemical changes in this breed that may modify the understanding of trypanotolerance. Fifteen WAD sheep were assigned into 3 groups (A, B, and C). Baseline (day 0) values of the parameters assayed were obtained before groups A and B were infected with Trypanosoma brucei brucei and Trypanosoma congolense , respectively, by intraperitoneal inoculation with 10 6 trypanosomes per animal. Standard procedures using Quimica Clinica Applicada (Spain) and Randox (UK) test kits were used to evaluate serum levels of AST, ALT, ALP, total protein, albumin, total cholesterol, urea, and creatinine on days 0, 14, 28, 42, 56, and 70 post infection. The infections caused sustained pyrexia, hypoproteinaemia, hypocholesterolaemia, weight loss, hepatitis, and mortalities although parasitaemia was greatly controlled especially in the T congolense infected rams. The findings suggest that the WAD rams are not just passive reservoirs of trypanosomes for human and animal infections, but experience active host-parasite interactions with huge price for resilience, biochemically.